The Implementation of Classroom-Based Assessment Using Instructional Coaching Model of Teacher Feedback Among Primary School English Teachers in West Aceh - Erizar Erizar; Rena Juliana; Abdul Gafur Marzuki; Astri Yulia; Nur Rohman (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
The research investigated challenges faced by English teachers in West Aceh, Indonesia, emphasizing the importance of effective professional development. The focus was on the impact of Classroom-Based Assessment (CBA) and instructional coaching on English teachers' performance in secondary schools. Employing a mixed-method approach with questionnaires and tests, the study targeted English teachers in secondary schools in West Aceh, with a sample of 50 teachers from 25 schools. Results revealed that instructional coaching significantly improved teachers' proficiency in providing feedback, covering aspects like classroom administration and student engagement. Notably, statistical analysis using the One Sample T-test showed a substantial enhancement in English instructors' feedback skills (P = 0.000 < 0.05) through instructional coaching. These findings had wide implications for the professional growth of English teachers in Aceh, with global relevance. The research contributes to the field of teacher professional development by providing empirical evidence on the effectiveness of integrating Classroom-Based Assessment with structured instructional coaching to strengthen feedback literacy among English teachers in secondary education. It also offers a contextualized model that can inform policy design, coaching frameworks, and sustainable professional learning programs in similar developing educational settings. The study suggested that instructional coaching was a powerful strategy to enhance teachers' feedback capabilities, positively impacting student outcomes. Teachers could draw valuable insights from this research to refine teaching methodologies and improve student learning experiences.